Institucionalização da escola pública em área rural: Joaçaba – SC (1938-1961) - Martinson, Célia Carmem (Universidade do Vale do Rio do Sinos, 2009)
This study focuses on the deployment and institutionalization process at the public primary school in the rural area of Joaçaba-SC between the years of 1938 and 1961. It analyses the educational public policies directed to this educational level and its role in the scholar culture formation. The public school in this region of Santa Catarina became public in 1938 when the primary education was nationalized both in the states and in the country. In that time, the schools in colonization areas, such as German-Brazilian in Santa Catarina, had their scholar cultural frame interrupted and disconfigured. From institutions with ethnic and denominational connotation, they got closed or were transformed in public institutions. This study analyses aspects related to the administrative organization, to the school maintenance and to the scholar area in relation to the scholar buildings. It covers also the challenges of teaching in rural areas as well as scholar, assessable and celebrational practices. The discussion is d
Keywords: educação rural; cultura escolar; história da educação; políticas públicas educacionais; escola primária pública; education history; educational public polices; rural education; scholar culture; public primary school; Ciências Humanas